The outrun [videorecording (DVD)] - Fingscheidt, Nora, 1983-; Liptrot, Amy; Lewis, Daisy; Ronan, Saoirse, 1994-; Essiedu, Paapa, 1990-; Elouahabi, Nabil; Hoyle, Izuka; Lyle, Lauren, 1992-; Reeves, Saskia; Dillane, Stephen, 1956-; Gürtler, John; Miserre, Jan; et al. (Sony Pictures Home Entertainment, 2024)
Based on the best-selling memoir by Amy Liptrot, The Outrun is set in the otherworldly Orkney Islands of Scotland. A brutally honest drama about addiction and recovery, strength and survival, mental health and the ability of the sea, the land and of people to restore life and renew hope. After a decade away in London, 29-year-old Rona returns home to the Orkney Islands. Sober but lonely, she tries to suppress her memory of the events which set her on this journey of recovery. Slowly the mystical land enters her inner world and one day at a time Rona finds hope and strength in herself among the heavy gales and the bracingly cold sea.